PENGARUH KOMPETENSI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DALAM MENINGKATKAN PELAYANAN PUBLIK DI KANTOR CAMAT BATURAJA TIMUR KABUPATEN OKU - Eca Novianty; Yunita Sari; Yetty Oktarina (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2026)
This study aims to analyze the influence of employee competence and the work environment on employee performance in improving public services at the East Baturaja Subdistrict Office in OKU Regency. The problem addressed in this study is the suboptimal performance of employees, which impacts the quality of public services. The research method employed is a quantitative descriptive approach. This study uses saturation sampling, or a census, in which the entire population of 45 employees was included as the research sample. The results of the study revealed that the calculation of the Competence variable (X1) against Employee Performance (Y) yielded a significance value of 0.000 < 0.05. Meanwhile, the Work Environment variable (X2) against Employee Performance (Y) yielded a significance value of 0.005 < 0.05. Simultaneously, a significant F-value of 0.000 < 0.05 was obtained. The R-squared value is 0.586. It can therefore be concluded that the independent variables—Competence (X1) and Work Environment (X2)—have a partial and simultaneous effect on Employee Performance (Y) of 58.6%, while the remainder is attributed to variables outside the scope of this study.